2014
DOI: 10.1007/s11010-014-2176-2
|View full text |Cite
|
Sign up to set email alerts
|

Short-term but not long-term hypoglycaemia enhances plasma levels and hepatic expression of HSP72 in insulin-treated rats: an effect associated with increased IL-6 levels but not with IL-10 or TNF–α

Abstract: The inducible expression of the 70-kDa heat shock proteins (HSP70) is associated with homeostatically stressful situations. Stresses involving sympathetic nervous system (SNS) activation, including α1-adrenergic agonists and physical exercise, are capable of inducing HSP70 expression and release of the HSP70 inducible form, HSP72. However, whether hypoglycaemia is capable of influencing HSP70 status under a stressful situation such as insulin-induced hypoglycaemia (IIH), which also involves SNS activation, is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 50 publications
2
17
0
Order By: Relevance
“…Recent studies have indicated that HSP70 status is intimately correlated with glycemic control and vice versa [21]. In other words, alterations in blood glucose may also interfere in HSP70 expression and its export toward the extracellular space.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have indicated that HSP70 status is intimately correlated with glycemic control and vice versa [21]. In other words, alterations in blood glucose may also interfere in HSP70 expression and its export toward the extracellular space.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, high levels of TNF-a and NFjB inhibited muscle hypertrophy, even though IL-6 levels were significantly increased. Ludwig et al [24] found that IL-6 increased through exercise could inhibit NFjB expression by activating HSP70, which can prevent muscle mass loss with aging. In trained young rats, IL-6 increased in response to a bout of downhill running, while TNF-a was unchanged in both sedentary and trained rats.…”
Section: Discussionmentioning
confidence: 99%
“…Within the HSP70 family, the constitutive heat shock cognate, HSC70 (or HSP73, encoded by the HSPA8 gene in humans), and its inducible form (HSP72, encoded by HSPA1A) have received more attention for their ubiquity and high level of expression. Although iHSP70 had been serendipitously discovered in heat-shocked Drosophila busckii cells by Prof. Ferruccio Ritossa in 1962 [65], HSP70 expression is associated with a variety of homeostatically stressful situations, not only heat [66]. It is noteworthy that the inducible expression of HSP72 is impressively and highly conserved in nature from bacteria to humans: in order to manage on chaperone and cytoprotective intracellular functions, at least 13 genes were identified in humans that are responsible for HSP70 family coding [35,38].…”
Section: Heat Shock Proteins and The Heat Shock Responsementioning
confidence: 99%